Investigating food preservation - Skok, Stephen; Video Education Australasia (Australia : Video Education Australasia, 2001)
This program investigates leading food preservation methods such as dehydration, hot and cold thermal processes and the more controversial process of irradiation
Title from title screen
Executive producer, Neil Barret ; camera, Walter Repich, David Waddington ; graphics, Reece Sanders ; editor, Stephen Skok
Presenter: Julia Martin
Keywords: Food -- Preservation; Food -- Storage